HUBUNGAN KONSTANTA ATENUASI DENGAN KONSTITUEN AIR PADA PERAIRAN PELABUHAN KARIMUNJAWA - MUHAMMAD ULIN NUHA; ABDUL BASITH; WIKANTI ASRININGRUM; GATHOT WINARSO; KUNCORO TEGUH KURNIAWAN (Department of Geodesy Engineering, Faculty of Engineering, Diponegoro University,Indonesia, 2019)
Satellite-derived bathymetry (SDB) is one of the techniques in remote sensing for extraction of ocean depth by utilizing optical imagery. Spectral data from the water column is needed for SDB process. One of SDB method is an analytical method requiring field spectral data, water attenuation, and water constituents for depth estimation processes. Spectral data and attenuation were acquired by TriOS Ramses spectrometer. Water constituents are taken from filtered water samples to be tested at the laboratory. The water constituents tested were chlorophyll, CDOM, TSS, and TOM. The depth value of bathymetry extraction is strongly influenced by light penetration behavior. This is influenced by the condition of water constituents. Water constituents affect the attenuation of water. The study gives results from 4 stations of attenuation measurement having a positive correlation with chlorophyll constituents. Chlorophyll has a positive correlation with other constituents (TOM, CDOM, and TSS). From the value of water attenuation, the water classification around Karimunjawa Port are clear water of type III and 1 which have a value of (PAR) is 0.111 m-1.